Implementasi Karakteristik Akad Murabahah pada Produk Pembiayaan KBB (Kendaraan Bermotor Barokah) di BMT UGT Nusantara Capem Socah - Affandi, Mahrus; Rahman, Taufiqur (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The development of Islamic banking has made many Islamic banks appear, including conventional banks, to participate in opening Islamic banking services, so that the use of murabahah contracts is increasingly used. However, the reality on the ground is that many people do not understand the implementation of murabahah contracts, so that many people still think that the practices of Islamic banks and Islamic financial institutions are not much different from those of conventional banks. BMT UGT Nusantara Capem Socah provides a variety of financing products that use murabahah contracts, one of which is KBB (Barokah Motorized Vehicles), where the characteristics of the implementation of this financing BMT provides goods that customers want which are obtained from dealers directly by BMT, then sold to customers by informing the price acquisition plus profits according to the agreement between the BMT and the customer. This research uses a qualitative approach to the type of descriptive research. Data collection techniques through interviews, documentation and literature studies. The results of the study show that the implementation of the characteristics of a murabaha contract in KBB financing at BMT UGT Nusantara Capem Socah is in line with the principle of a Murabahah contract which makes BMT a supplier of goods which is used as the object of a murabaha contract that sells goods with legal ownership status, then sells them to customers at the cost price. plus profits according to the agreement of both parties and in its application using the first type, namely the consistent type of muamalah fiqh.